Addressing unmet needs in osteoarthritis - Martel-Pelletier, Johanne; Pelletier, Jean-Pierre, physician (Future Medicine Ltd (Unitec House, 2 Albert Place, London N3 1QB, UK), 2012)
Osteoarthritis, the most prevalent form of arthritis, is a leading cause of chronic disability worldwide and a major public health issue. Here, internationally renowned authors, from multiple specialties, analyze, dissect and provide a comprehensive update on this disease.